Assessment of Tax Expenditures in Turkey in Terms of Taxation Functions: 2019-2023 - Mutlu Yoruldu (Maliye Çalışmaları Dergisi)
It can be stated that the state has turned to the non-financial functions of taxation with the tax expenditure practices, with the abandonment ofa part of the current period tax collection. Purpose of tax expenditures can be explained by the aim of improving macroeconomic indicators such as economic growth, economic stability, efficiency in resource distribution and ensuring fair income distribution. Tax expenditures are generally incurred as tax exemptions, tax exemptions and tax deductions in tax practices. The tax system within the tax expenditure, size of the system and it is important for distribution as tax types in Turkey. The state forgoes tax receivables in the short term and leaves the collection of tax receivables to the long term, with the tax expenditure practices. It focuses on the economic and social objectives of taxation in the short term. Especially with the improvement of macroeconomic indicators, more tax revenues will be collected in the long term. This study aims to include the financial period 2019 to 2023 of tax expenditures in Turkey is evaluated using a variety of indicators and economic size in terms of the functions of taxation. Analyzes were made using the descriptive model, one of the qualitative research methods, and the documentation analysis technique, one of the research techniques. As a result of the study Turkey’s 2023 targets for moving towards that in this process it was concluded that income tax is a direct tax and corporate entities located in tax expenditure item in the tax to determine a plan of effectively used as a fiscal tool.